A case of duodenal hemorrhage due to arteriovenous malformation around a serous cystic neoplasm - Shunsuke Tamura; Yusuke Yamamoto; Yukiyasu Okamura; Teiichi Sugiura; Takaaki Ito; Ryo Ashida; Katsuhisa Ohgi; Nobuyuki Watanabe; Keiko Sasaki; Takashi Sugino; Katsuhiko Uesaka (Surgical Case Reports)
Abstract Background No reports have so far described arteriovenous malformation (AVM) in the pancreas caused by a tumor. We herein report a case of pancreatoduodenectomy for a patient who developed duodenal hemorrhage due to AVM developed around serous cystic neoplasm (SCN) of the pancreas. Case presentation A 79-year-old man was referred to our hospital because of anemia (Hb 7.4 g/dl) and pancreatic head tumor. Computed tomography showed microcystic-type SCN, 87 mm in size, in the pancreatic head. Vascular hyperplasia had developed around the cystic lesion. Upper gastrointestinal endoscopy and colonoscopy did not reveal the cause of anemia, so the patient was followed closely without hemostatic therapy. Iron preparations had improved the anemia. Three months later, the patient developed anemia (Hb 5.8 g/dl) again. Gastrointestinal endoscopy showed oozing from the mucosa in the duodenum via the swollen vascular hyperplasia. He was diagnosed as duodenal hemorrhage from the blood vessels around SCN. Pancreatoduodenectomy was performed to control repeated duodenal bleeding. A histopathological examination revealed that the cystic lesion in the pancreatic head was SCN, and the AVM developed around SCN and duodenum, causing repeated duodenal hemorrhage. The patient was discharged on postoperative day 22. Nine months after surgery, the patient had no recurrence of anemia. Conclusions There have been no reports of duodenal hemorrhage due to acquired pancreatic AVM around pancreatic tumor, including SCN. We successfully treated a case of duodenal hemorrhage due to pancreatic AVM around SCN by pancreatoduodenectomy.